THE EFFECTS OF IMAGE STREAMING STRATEGY IN LEARNING TO WRITE NARRATIVE ENGLISH TEXT BY YEAR 11 STUDENTS OF SMA NEGERI 1 TINAMBUNG KAB. POLEWALI MANDAR - Hijrah Tul Muntaha; Kisman Salija; Munir Munir (Universitas Negeri Makassar, 2022)
The purpose of this study was To Find Out whether or not the Image Streaming Strategy affects the student’s narrative English text. This study used Pre-Experimental in quantitative methods and image streaming was used as a research strategy. The population in this study were students of class XI IPA SMA Negeri 1 Tinambung. in the 2021/2022 school year. Samples were taken using a cluster random sampling technique consisting of 29 students. The instrument of this research is a Writing test of a sheet essay writing short story. From the analysis of data and computations, it was found that the image streaming strategy has an effect on the skills writing narrative English text for class XI Students of SMA Negeri 1 Tinambung. The result writing skill narrative text by students before use image streaming strategy was 53.17 in the poor category and after using the image streaming strategy was 89.73 in the Good category. This means that there is the effect of Image Streaming strategy in learning to write narrative English text for XI Students SMA Negeri 1 Tinambung.